OP0226 Randomized, Double-Blind Study Comparing Chs-0214 with Etanercept in Patients with Active Rheumatoid Arthritis (RA) despite Methotrexate (MTX) Therapy. (15th July 2016) - O'Dell, J.; Takeuchi, T.; Tanaka, Y.; Louw, I.; Tiabut, T.; Kai, M.; Oribe, M.; Nakashima, S.; Finck, B.; ,
Abstract : Background: CHS-0214 is a proposed biosimilar of etanercept, a fusion protein inhibiting tumor necrosis factor that is approved for several inflammatory autoimmune diseases. Objectives: This Phase III multi-center study compared the efficacy, safety, and immunogenicity of CHS-0214 with etanercept for 24 weeks (Part 1) in patients with moderate/severe RA who had an inadequate response to MTX; then all patients received open-label CHS-0214 for 24 weeks with a final evaluation at Week 52 (Part 2). Methods: Patients were randomized to 50 mg of CHS-0214 or etanercept subcutaneously QWx24 weeks (Part 1). The primary endpoint was the ACR20 response rate at Week 24. To establish the equivalence of CHS-0214 to etanercept, the 95% confidence interval (CI) of the treatment difference between groups had to be within [–15%, 15%]. Secondary efficacy endpoints (ACR50, ACR 70, and change in DAS28-CRP), safety, and immunogenicity were also evaluated. Results: In 13 countries, 644 patients on MTX were randomized and received treatment. Baseline characteristics were comparable between treatment groups. Part 1 results are reported here. At 24 weeks, 512 patients were evaluable for efficacy. The ACR20 response rate was 91.0% (233/256) in the CHS-0214 group and 90.6% (232/256) in the etanercept group. The 95% CI of the treatment difference was [- 4.55, 5.37], which was within the pre-defined equivalence range. The response rates at 24 weeks were 67.6% vs. 63.7% for ACR50 and 38.3% vs. 37.9% for ACR70 in the CHS-0214 and etanercept groups, respectively. Mean (±SD) DAS28-CRP scores were 5.45 (± 1.00) and 5.42 (±1.00) at baseline and decreased to 2.67 (± 1.18) and 2.73 (±1.14) at 24 weeks in the CHS-0214 and etanercept groups, respectively (See Figure ). Among the 644 patients, adverse events (AEs) occurred in 60.8% and 65.0% of patients in the CHS-0214 and etanercept groups, respectively, including all infections combined in 34.3% and 32.2%, respectively. Investigator-designated treatment-related AEs occurred in 16.4% and 21.9% of patients, respectively, and most commonly included: injection site reactions (2.2% and 13.4%) and all infections combined (7.7% and 5.3%). Treatment-related serious AEs occurred in 3 (0.9%) patients treated with CHS-0214 (cholecystitis, increased blood creatinine phosphokinase, and bronchospasm) and 1 (0.3%) patient treated with etanercept (sepsis). Binding anti-drug antibodies occurred in 1.3% and 4.7% of patients in the CHS-0214 and etanercept groups. Conclusions: These results demonstrated equivalence of CHS-0214 to etanercept with respect to efficacy as measured by the primary endpoint (ACR20 at Week 24) and other measures (ACR50, ACR70, and DAS28-CRP). CHS-0214 was well tolerated with no clinically meaningful differences to etanercept with regard to safety and immunogenicity. Disclosure of Interest: J. O'Dell: None declared, T. Takeuchi: None declared, Y. Tanaka: None declared, I. Louw: None declared, T. Tiabut: None declared, M. Kai: None declared, M. Oribe: None declared, S. Nakashima Employee of: Daiichi Sankyo Co., Ltd., B. Finck Shareholder of: Coherus Biosciences, Employee of: Coherus Biosciences